EVALUATING SERVICE QUALITY DIMENSION USING IMPORTANCE AND PERFORMANCE ANALYSIS AT J’CO AND DONUTS COFFEE MANADO TOWN SQUARE - Walewangko, Natasha C.; Lapian, S.L.H.V Joyce; Tumewu, Ferdinand . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: In the highly competitive of food industry, especially for dessert and beverages restaurant, service becomes one of the most important things for gaining sustainable competitive advantages in the marketplace. Service quality is a focused evaluation that reflects the customer’s perception of specific dimension of service; reliability, responsiveness, assurance, empathy and tangibles. The objective of this research is to know the importance and performance of service quality at J’Co Donuts and Coffee Manado Town Square by using an Importance and Performance Analysis (IPA). The population observed is the customer of J’Co Donuts and Coffee Manado Town Square with sample size as many as 100 respondents. The key result were the importance of service quality in J’Co Donuts and Coffee Manado Town Square is some of the services considered extremely important to customers but the company are have not ability yet to get high customer satisfaction and the performance of service quality has a low performance and did not meet customer expectation. Thus, the quality of services should improve immediately and develop improvement strategies to enhance customer satisfaction.Keywords: service quality, customer satisfaction, importance and performance analysis.